In vitro study of the stretching time-associated force magnitude generated by NiTi and stainless-steel closed coil springs - Ongko, Jennifer Xavier; Yusuf, Muslim; Bahirrah, Siti (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Closed coil spring is an additional tool in a fixed-orthodontic treatment. NiTi is an orthodontic alloy that has shape memory and elasticity features, while stainless steel has properties of malleability, low friction between wire-bracket, as well as easy soldering and welding. Various properties of closed coil springs have been widely studied, but research on the stretching time remains unclear. This study aimed to determine the effect and differences in the stretching time for 7 days, 14 days, 21 days, and 28 days on the force magnitude of NiTi and stainless-steel (SS) closed coil spring. A 7 x 5 x 1 cm acrylic blocks with 1 cm acrylic posts were employed, and 25 mm closed coil springs were attached to the acrylic posts using modified T-sticks. The springs were immersed in an artificial saliva with pH of 6.75 for 7, 14, 21, and 28 days in an incubator at 37 °C. The container was removed from the incubator and the force was measured using a universal testing machine. Kolmogorov-Smirnoff test was carried out to analyze parametricdata, while independent T-test was used to determine the difference between each group. There was a significant effect of stretching time on the force magnitude of the SS closed coil spring in all the groups (p < 0.05). There was no significant effect of stretching time on the force of the NiTi closed coil spring on days 7, 14, and 21 (p > 0.05) but there was a significant effect on day 28 (p < 0.05). A significant effect between the ratio of the SS and NiTi closed coil spring (p < 0.05) was confirmed. Longer stretching time indicated a force loss in the SS closed-coil spring, while the NiTi spring had a more stable force which implies a formidable treatment-time for orthodontic treatment.